2014
DOI: 10.1590/0103-6440201300125
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Factors Associated with Orthodontic Microscrew Failure

Abstract: The objective of this study was to examine whether factors such as insertion site, patient's facial pattern, microscrew features, type of tooth movement desired, level of experience handling orthodontic microscrews and operator expertise were associated with failure of microscrews. After the approval of an ethics committee, 166 patients of one practice signed an informed consent and received 293 microscrews randomly distributed by 3 operators with different levels of practical experience and expertise in handl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 24 publications
1
12
0
1
Order By: Relevance
“…In most of the studies mean patient age was around 25 years, samples generally consisting of predominantly young adults. Of the 26 articles, 7 were prospective studies [15][16][17][18][19][20][21] and 19 retrospective [11][12][13][14][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] . Follow-up periods ranged from approximately 18 months to 2 years.…”
Section: Results Of Individual Studies Meta-analysis and Additional mentioning
confidence: 99%
See 1 more Smart Citation
“…In most of the studies mean patient age was around 25 years, samples generally consisting of predominantly young adults. Of the 26 articles, 7 were prospective studies [15][16][17][18][19][20][21] and 19 retrospective [11][12][13][14][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] . Follow-up periods ranged from approximately 18 months to 2 years.…”
Section: Results Of Individual Studies Meta-analysis and Additional mentioning
confidence: 99%
“…www.nature.com/scientificreports www.nature.com/scientificreports/ between mini-implant failure and age. Some studies found no association between age and failure 14,15,32 , while others found that the patient's age could influence mini-implant failure because younger patients present finer cortical bone and lower bone density 19,[30][31][32][33][34] . (Fig.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…An important accent was focused on the site of surgery. As showed in Figure 2, a larger number of implants were placed in the maxilla rather than in the lower jaw, thus increasing the success rate in the maxilla in all but ten studies [6,[9][10][11][12][13][14][15][16][17].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have evaluated factors responsible for the failure of miniscrews. 13,14 Failure of miniscrews might be due to inflammation resulting from a poor bone-screw contact; 10 however, hostrelated factors such as age, gender, and cortical bone quality and thickness, and miniscrew-related factors such as diameter and length are considered important factor for the primary stability of miniscrews. [15][16][17] One of the techniques used to evaluate the primary stability of miniscrews is to measure insertion torque at the time of screw placement.…”
Section: Introductionmentioning
confidence: 99%